The Voyageur François in Hungary - Le Mao, Caroline (Historical Studies on Central Europe, 2024)
In the forty-two volumes of Voyageur François, ou la Connaissance de l’Ancien et du Nouveau Monde (1765–1795), Abbé Delaporte devoted a few pages to Hungary. Through fictitious letters, the polygrapher produced a compilation that provides a glimpse of what a French nobleman wishing to discover Hungary might know. This is what we propose to analyse, by considering his historical approach, which reveals his biases, by examining the picture he paints of Hungary’s towns and countryside, and then by focusing on his presentation of Hungarian customs (peoples, languages, religion, etc.).